1898
DOI: 10.1152/ajplegacy.1898.1.2.164
|View full text |Cite
|
Sign up to set email alerts
|

A Further Study of the Influence of Alcohol and Alcoholic Drinks Upon Digestion, With Special Reference to Secretion

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…They confirmed the original report of Chittenden et al (1898), that is, the introduction of alcohol into the stomach resulted in the secretion of acid gastric juice. We also showed the stimulatory effect of ethanol administered intragastrically on gastric acid secretion in dogs.…”
Section: Discussionsupporting
confidence: 84%
“…They confirmed the original report of Chittenden et al (1898), that is, the introduction of alcohol into the stomach resulted in the secretion of acid gastric juice. We also showed the stimulatory effect of ethanol administered intragastrically on gastric acid secretion in dogs.…”
Section: Discussionsupporting
confidence: 84%
“…It is about 100 years ago that a stimulatory effect on gastric acid secretion was suggested after uncontrolled experiments with alcohol [57,58] . Beginning in the early 1980s and using systematic and controlled examinations on the effect of pure ethanol and commonly ingested alcoholic beverages on gastric acid secretion, Singer and co-workers [59][60][61][62][63][64][65][66][67] found that the effect of ethanol and alcoholic beverages on gastric acid secretion in healthy humans is differentiated after all.…”
Section: Gastric Acid Secretionmentioning
confidence: 99%
“…Indeed, since the end of the last century [3], it has been accepted that the ingestion of ethanol stimulates gastric secretion. The excitatory mechanism is not entirely clear but several studies suggest that at least two main paths are involved.…”
Section: Abstract the Effects Of Intragastric Administration Of Ethamentioning
confidence: 99%